Risk Factors For Post-Tonsillectomy Hemorrhage - Susaman, Nihat; Kaygusuz, Irfan; Karlidag, Turgut; Keles, Erol; Yalcin, Sinasi; Cilibas, Rabia Efe (Deomed Publ, Istanbul, 2018)
Objectives: This research was undertaken to determine the frequency of post-tonsillectomy hemorrhage (PTH) in one particular clinical setting and to assess which risk factors exist for PTH. Methods: Following a retrospective case review of 892 patients who had gone through either tonsillectomy or adenotonsillectomy, a subgroup of 50 records were selected for detailed study. These 50 patients were then classified as either pediatric cases (aged under 16) or adult cases (aged over 16). Their risk factors were then assessed. Risk factors included: age, sex, surgical indication; type of surgery; time hospitalized post-operatively; timing of PTH (primary and secondary); management used to staunch bleeding and time in hospital following PTH. Results: The overall rate of PTH was 5.6% (3.0% pediatric, 2.6% adult). All PTH instances were secondary and no primary type occurred. In comparing the adult and pediatric cases of PTH, there was no statistically significant difference (p>0.05) in terms of age, sex, time hospitalized post-operatively, management used to staunch bleeding or time in hospital following PTH. There was, however, a statistically significant difference (p<0.05) between groups in terms of surgical indication and timing of PTH (primary or secondary). Conclusion: There was an increased frequency of secondary PTH in both groups. PTH typically happened between day 5 and 10 post-operatively. Patients need to be advised about this risk and show caution regarding factors that increase the risk of PTH after surgery.
Keywords: Tonsillectomy; postoperative hemorrhage; pediatrics; adults